Pengaruh Pelatihan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Metropolitan Kentjana Tbk - Dwi Lestari, Mutia; Siska, Elmira; Indra, Natal (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to determine how much influence work training and work discipline have on employee performance at PT Metropolitan Kentjana Tbk (Pondok Indah Golf Apartment Unit). The research method used is a quantitative method approach with data collection techniques using purposive sampling with a total sample of 50 respondents. Primary data was collected using a questionnaire in Likert scale units. Data processing uses SPSS 25 software for instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results showed that partially, job training has a positive and significant relationship to employee performance. Work discipline also has a positive and significant relationship to employee performance. Then, through training tests simultaneously, both variables, both work and work discipline have a positive and significant relationship to employee performance.